Midwives in China: 'jie sheng po' to 'zhu chan shi' - Harris, A.; Belton, S.; Barclay, Lesley; Fenwick, Jennifer (Elsevier, 2009)
We explore the position of midwifery in contemporary China, and draw on fieldwork conducted in Shanxi and Sichuan Provinces during 2005 and 2006, the available literature in English and to a lesser extent in Mandarin. We also explore the historical antecedents to the present-day professional status, practices and position within the health care system of midwifery in China. We consider the effect on midwifery of the place of biomedicine in the modernising project of the post-reform State, the shift of birth from the private to the public domain, the rise of the medical profession, the medicalisation of birth and the increasing use of technology, and trace changes in the nature of relations between midwives, doctors and the State from Imperial China to the present day. In particular, we examine the changes that have occurred as midwifery has moved from the arena of the lay practitioner (‘jie sheng po’) to the professional (‘zhu chan shi’). We draw out and critique some ways that midwives act to differentiate themselves and lay claim to a variant body of practice-based knowledge, yet question the capacity of midwifery in China today to assert, in any substantial way, a professional identity that distinguishes it from medical obstetric practice.